2010
DOI: 10.1159/000276589
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of T Cell Proliferation by Root Apical Papilla Stem Cells in vitro

Abstract: The use of allogeneic stem cells strongly extends the range of stem cell applications in dentistry; however, immunological rejection remains a major concern. There is little information about the immunological features of dental-related stem cells in the literature. Therefore, we investigated the immunological characteristics of stem cells from the root apical papilla (SCAP) of swine in vitro by measuring T cell immunomodulation and apoptosis. We found that SCAP expressed a low level of swine leukocyte antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 65 publications
3
45
0
3
Order By: Relevance
“…In addition, cSCAP of miniature pig possessed the similar proliferation rate, differentiation potential, and immunomodulatory function as seen in fSCAP. This study demonstrates that cryopreservation does not affect the biological and immunological properties of SCAP, supporting the feasibility of SCAP cryopreservation in nitrogen (Ding et al, 2010).…”
Section: Stem Cells In Dental Fieldsupporting
confidence: 67%
See 1 more Smart Citation
“…In addition, cSCAP of miniature pig possessed the similar proliferation rate, differentiation potential, and immunomodulatory function as seen in fSCAP. This study demonstrates that cryopreservation does not affect the biological and immunological properties of SCAP, supporting the feasibility of SCAP cryopreservation in nitrogen (Ding et al, 2010).…”
Section: Stem Cells In Dental Fieldsupporting
confidence: 67%
“…Thus, one dental MSCs-SCAP was investigating the immunogenicity and immunomodulatory effects in a swine dental model. They found that SCAP were weakly immunogenic and suppressed T cell proliferation in vitro through an apoptosisindependent mechanism (Ding et al, 2010).…”
Section: Stem Cells In Dental Fieldmentioning
confidence: 99%
“…Both DPSCs and PDLSCs are derived from mesenchymal tissue like bone marrow mesenchymal stem cells (BMMSCs), which show low immunogenicity and immunomodulation functions [7]. Similar to BMMSCs, dental MSCs, including PDLSCs, DPSCs, and SCAP possess immunomodulatory effects in vitro [27,28]. Furthermore, we previously established a novel approach for using allogeneic PDLSCs to cure periodontitis in a minipig model of periodontitis in vivo [9].…”
Section: Figmentioning
confidence: 99%
“…Notably, SHED are the first MSCs derived from human exfoliated tissue, a very accessible tissue resource (Miura et al, 2003). (2) Dental MSCs, including SHED, SCAP, PDLSCs and jaw bone MSCs, show a strong immunomodulatory capacity, possibly because of the high frequency of exposure to the inflammatory environment in the oral cavity (Wada et al, 2009;Ding et al, 2010a;Yamaza et al, 2010Yamaza et al, , 2011. (3) Because of their neural crest origins, dental MSCs show robust multi-potential differentiation capabilities, benefiting the regeneration of orofacial tissues in orofacial context (Chung et al, 2009;Yamaza et al, 2011).…”
Section: Msc Immunomodulatory Properties Contribute To Oral Disease Tmentioning
confidence: 99%